Politics and Policy: Measuring the effect of the Child Care Tax Rebate on childcare affordability - Baker, D (My University, 2012)
Childcare affordability is a perennial issue. Using data collected in the Household, Income and Labour Dynamics in Australia (HILDA) Survey this paper analyses the trend in reported difficulties between 2001 and 2010 with the cost of childcare. In response to popular concern about the rising cost of childcare the incumbent Howard Government announced the Child Care Tax Rebate during the 2004 election campaign. The policy provided a capped 30 per cent tax rebate to all families using formal childcare. At the 2007 election the Opposition campaigned on raising the rebate to 50 per cent and was elected to form government. This article measures the proportion of household disposable income spent on childcare costs and compares this cost:income ratio with reported difficulties to assess the effectiveness of this policy in making childcare more affordable. The potential influence of increased debate about childcare affordability and policy responses during election campaigns is also considered. It is concluded that this policy has at best provided only short-term benefits to families and that reported cost difficulties appear to be affected in some part by policy announcements.
Public Policy
Keywords: Child Care -- Cost/affordability; Benefits and Payments; Families and relationships; Child Care; Benefits and Payments; Cost/affordability; Families and relationships